Elitismo, violencia y degeneración física en los diagnósticos de las derechas argentina y chilena (1880 – 1945) - Daniel Lvovich; Ernesto Bohoslavsky (Nuevo mundo - Mundos Nuevos, 2009)
This article analyzes some of the right and extreme right-wing’s discourses and interpretations in Argentina and Chile, between the end of the nineteenth century and WWII. Some attention is focused on the way some rightist figures (especially physicians, politicians and intellectuals) perceived the physical and moral decadence of their respective nations. In their imagination, the other side of the decadence process would be a moralistic Crusade aimed at imposing a new transcendental and anti-decadent order.